Validity of Animated Video-Based Learning Media Development Using Adobe After Effect Application in Grade IV Elementary School - Miranda; Taali; Irdamurni; Abdul Habib Arrasyidi Desky; Ganefri (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop Indonesian language learning media based on animated videos created with Adobe After Effects for fourth-grade elementary school students. The research employed a Research and Development (R&D) approach using the 4D development model. The research subjects consisted of media experts, material experts, linguists, and Focus Group Discussion (FGD) participants. Data were collected through observation sheets, interview questionnaires, and validation instruments, and analyzed using qualitative and quantitative descriptive techniques. Validation results from experts indicated that the developed media was categorized as “very valid” in all aspects, including media (88.00), material (94.00), and language (90.00). The results of FGDs with teachers showed that the learning media was highly feasible for classroom use, with scores for content feasibility (91.60), language accuracy (92.00), presentation (85.60), and graphics (93.50), resulting in an overall average score of 90.69. The developed media meets key characteristics of effective learning media, as it is engaging, easy to operate, and supports meaningful learning processes. In conclusion, animated video-based learning media using Adobe After Effects is valid, feasible, and appropriate for use in Indonesian language learning at the elementary school level.